PENGUKURAN ANTROPOMETRI PEKERJA CUT OPEN PADA PROSES PENGOLAHAN SUSU DI PT. XYZ - Asy'ari, Subchan (Journal Knowledge Industrial Engineering (JKIE), 2019)
The process of milk processing at PT XYZ is done manually and the tools used are not ergonomic, workers do the processing process that is cut open in a standing position and have to move their hands repeatedly so that if the milk produces the best milk quality, the purpose of this study was conducted with the aim to can provide several advantages one of which simplifies the cut open work process. So that workers can do their jobs easier, more comfortable, more focused at work and most importantly can reduce the impact of fatigue, back and shoulder pain due to lack of facilities. This research was conducted to obtain target specifications for the manufacture of assistive chairs for milk processing according to the Anthropometric approach and the physical form of the worker. Anthropometric data collection was carried out randomly and 10 sample / person data were taken from workers at PT XYZ. From the results of data processing to determine the dimensions / size of milk processing workers is the size of the chair that is the width of the base of the chair 39.39; seat height 44.73; the length of the seat base 43.29 and the height of the seat backrest 58.59. With an ergonomic assist chair, workers can more easily process milk compared to using a knife, removing the contents of the product (milk) in the container that has been